School Pastoral in Preparation for Priesthood Duties: Strengthening the Pedagogical and Spiritual Competence of Students of the Faculty of Philosophy - Laurentius Tinambunan (Abdimas Paspama, 2023)
School pastoral is an important part of the formation of prospective priests because it brings together the learning of philosophy and theology with concrete experience accompanying students. This Community Service activity was carried out in the context of the Education and Student Orientation (ORDIK) for new students of the Faculty of Philosophy, Catholic University of Saint Thomas on August 7-11, 2023. The material "School Pastoral as Preparation for Priesthood Duties" was delivered by Dr. Laurentius Tinambunan and attended by 80 level I students who were recorded on the attendance list. The activity aims to strengthen students' understanding of school pastoral as a form of Church service, improve pedagogical and communication readiness, and foster teaching spirituality as part of priesthood duties. The approach used is educational, reflective, participatory, and contextual through scientific lectures, interactive discussions, case studies, learning communication exercises, pastoral reflection, and written evaluation. The results of the activity show the development of the school's pastoral paradigm as a work of evangelization, an increase in pedagogical insight, an increase in readiness to face the classroom, a growing awareness of the importance of dialogue and student assistance, and the formation of a commitment to carry out pastoral practices as a service. The validity of the implementation is verified through assignment letters, ORDIK schedules, attendance lists, event minutes, and resource person certificates. This article presents the results descriptively because the activity document does not contain individual pre-test and post-test scores.